Rhodium(III)-catalyzed direct C-7 sulfonamidation and amination of indolines with arylsulfonamides and trifluoroacetamide. Issue 20 (16th May 2019) - Dong, Yaqun; Sun, Song; Yu, Jin-tao; Cheng, Jiang
Graphical abstract: Highlights: Rhodium-catalyzed direct C-7 sulfonamidation and amination of indolines. Simple arylsulfonamides and trifluoroacetamide used as amide source. Catalytic system is highly convenient on mmol scale. Abstract: A rhodium-catalyzed direct C–H sulfonamidation and amidation of C-7 position of indolines by simple and commercially available arylsulfonamides and trifluoroacetamide has been developed, affording a series of N -arylsulfonamides and N -aryltrifluoroacetamides in moderate to excellent yields, respectively. Notably, this catalytic system is highly convenient on mmol scale.